Developing An Enhanced Maqasid Shariah Index in Measuring the Performance of Zakat Institutions (S/O 21027) - Harun, Siti Latipah; Abd Wahab, Norazlina; Yusuff, Noraini; Bahaman, Muhamad Abrar; Abdul Haniff, Hazwan Syah Niezam (UUM, 2023)
Pandemic Covid 19 causes many people to be affected financially. They are facing financial constraints due to losing their job. The movement control order makes their spending increase due to working at home, especially electricity bills, and other utilities fees. Therefore, zakat institutions are among the important bodies that play a major role specially to assist asnaf, their staff and also community to protect human well-being. The aims of establishment of Zakat institutions are to manage zakat in Muslim countries. Zakat institutions play a key role in promoting the socio-economic objectives of zakat in Malaysia. This parallel to the Maqasid Shariah whereby Maqasid shariah emphasis on the protection of human well-being through five elements which are protection of faith, protection of self, protection of intellect, protection of posterity and protection of wealth. This conceptual paper highlights the Maqasid Shariah elements as suitable measurement to be used as index or benchmark by zakat institutions to enhance the future performance of zakat institutions in line with Maqasid shariah. To fulfil the objective of study, literature search and the best practice of Maqasid shariah elements were selected and the theoretical framework designed.